Adolescent Offending and the Segregation of Poverty in Urban Neighbourhoods and Schools: An Assessment of Contextual Effects from the Standpoint of Situational Action Theory. (22nd November 2011) - Pauwels, Lieven
Abstract : Contextual research on adolescent offending is primarily based on the idea that residential areas provide a major ecological setting that (indirectly) shapes observed differences in adolescent offending. The social disorganisation/collective efficacy perspective has tried to explain why structural disadvantage of residential areas affects residents' involvement in offending. On the other hand, contextual research has also been conducted within the school setting. This separate contextual approach is problematic as it does not reflect the reality of adolescents' lives. Adolescents are exposed to different ecological settings. They are also exposed to many other settings that may provide opportunities to offend, as outlined in the situational action theory (SAT) of crime causation. This study contributes to the literature on the urban context of offending in three ways. First, the effects of adolescents' residential neighbourhood and school context on adolescent offending are assessed simultaneously. Second, this study elaborates on SAT from a cross-level point of view. Third, this contribution makes use of non-hierarchical multilevel modelling, which is a statistically correct method of testing hypotheses that involve multiple contexts. Our study revealed the existence of small contextual effects of school-level disadvantage, whereas the effect of neighbourhood-level disadvantage is entirely due to neighbourhood composition.